Specimen Preparation Technique for Polymeric Materials - Gan, P. F.; Ngui, C. L. (Malaysian Journal of Science, 2008)
A simple and cost-effective specimen preparation technique, using two chrome washers to sandwich the specimen has been adopted to assess polymeric materials under the Scanning Electron Microscope (SEM). Areas of interest on both sides of the same specimen can be examined by simply flipping over this specimen assembly to the other side after the initial surface has been viewed. In the conventional specimen preparation mounting on conductive carbon tape, different specimens are required if both surfaces need to be studied. This new technique has greatly helped in investigations of the failure modes on polymeric films and in the understanding of the degradative impact of chemical or mechanical agents on both sides of the polymeric films. In addition, this simple specimen preparation technique also provides a solution for viewing thin and soft polymeric materials such as condoms in which the suspension of the condom between the chrome washers has been shown to largely eliminate artifacts as reported by Rosenzweig et al.